Service Quality - Determining Factors - Žalimienė, Laimutė (Socialinė teorija, empirija, politika ir praktika, 2001)
The goal of the paper is to present the development of social service system in Lithuania. The first period is from 1990 to 1998. It is stated that the first period is characterized by the rapid increase in the amount of social services. The second period started in 1998 and its distinguishing characteristic is an attention to the quality of social services. The issues and difficulties of quality measurement are discussed in the last part of the paper.
Keywords: Social services; Development; Quality; Lithuania